Application of Enzymes in Dairy Processing Industry: A Review - Kumar, Akash; Jangra, Aarzoo; Pramanik, Jhilam (Current Nutrition & Food Science, 2022)
Enzymes are proteins and bio-catalysts. They are responsible for initiating a specific response to a specific outcome. In the dairy industry, numerous enzymes are used, such as rennet and proteolytic enzymes. These enzymes are used for the coagulation and ripening of cheese. Enzymes are also used to increase the nutritional value of dairy products to alleviate the state of malnutrition. This review paper converges on the utilization of different enzymes in the dairy processing industry.
Keywords: biocatalyst